Floral Diversity Of Mangrove Forest In The Kaliuntu Bay- Rembang Based On Palynological Evidences - SRI WIDODO AGUNG SUEDY; TRI RETNANINGSIH SOEPROBOWATI; A. TJIPTO RAHARDJO; KHOIRIL ANWAR MARYUNANI; RACHMAD SETIJADI (Biodiversitas Journal of Biological Diversity, 2006)
Palynological evidences (polen and spores) have been used to study mangrove diversity of coastal zone sites at Kaliuntu bay (Rembang), province of Central Java. Data was collected in April 2nd to April 17th 2005, following transect method. In this research for sediments sampling used surface-subsurface sampling method (depth in 10cm). The result showed that mangrove forest in the coastal zone of Kaliuntu bay (Rembang) was dominated by Rhizophoarceae polen type (included Rhizophora genera)Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: palynological evidences; diversity; polen type